Fisetin Attenuated Oxidative Stress-Induced Cellular Damage in ARPE-19 Human Retinal Pigment Epithelial Cells Through Nrf2-Mediated Activation of Heme Oxygenase-1 - Park, Cheol; Noh, Jeong Sook; Jung, Youngmi; Leem, Sun-Hee; Hyun, Jin Won; Chang, Young-Chae; Kwon, Taeg Kyu; Kim, Gi-Young; Lee, Hyesook; Choi, Yung Hyun (Frontiers in Pharmacology, 2022)
Fisetin is a kind of bioactive flavonol, widely present in various fruits such as strawberries and apples, and is known to act as a potent free radical scavenger. However, the mechanism of action related to the antioxidant activity of this compound in human retinal pigment epithelial (RPE) cells is not precisely known. In this study, we aimed to investigate whether fisetin could attenuate oxidative stress-induced cytotoxicity on human RPE ARPE-19 cells. To mimic oxidative stress, ARPE-19 cells were treated with hydrogen peroxide (H2O2), and fisetin significantly inhibited H2O2-induced loss of cell viability and increase of intracellular reactive oxygen species production. Fisetin also markedly attenuated DNA damage and apoptosis in H2O2-treated ARPE-19 cells. Moreover, mitochondrial dysfunction in H2O2-treated cells was alleviated in the presence of fisetin as indicated by preservation of mitochondrial membrane potential, increase of Bcl-2/Bax expression ratio, and suppression of cytochrome c release into the cytoplasm. In addition, fisetin enhanced phosphorylation and nuclear translocation of nuclear factor erythroid 2 related factor 2 (Nrf2), which was associated with increased expression and activity of heme oxygenase-1 (HO-1). However, the HO-1 inhibitor, zinc protoporphyrin, significantly reversed the protective effect of fisetin against H2O2-mediated ARPE-19 cell injury. Therefore, our results suggest that Nrf2-mediated activation of HO-1 may play an important role in the antioxidant activity of fisetin in RPE cells, contributing to the amelioration of oxidative stress-induced ocular disorders.